"THE ROLE OF INTERFIXES IN LANGUAGE DEVELOPMENT AND EDUCATION PROCESSES" (Journal of Universal Science Research, 2025)
This research is aimed at studying the role of interfixes in language development and their significance in educational processes. This research analyzes how interfixes assist students in the language learning process, simplify pronunciation, and improve word formation. This study helps deepen the understanding of the impact of interfixes on language learning in educational settings and serves as a basis for introducing new methods in language teaching.